Navigating expectations for sustainable product design: a discursive psychology analysis of designers’ accounts - Cooper, Liz (The University of Edinburgh, 2023)
Sustainable design is vital to achieving sustainable development. It is commonly argued that designers should ensure more sustainable design decisions are made, based on environmental values, and should take responsibility for the sustainability of product outcomes. In this thesis, I treat decision-making, personal values, and responsibility as psychological concepts, thus examining the setting of sustainable design through a psychological lens. I argue that the ways these concepts are talked about in design literature construct expectations regarding how designers should act. However, there is ambiguity in this literature regarding what the designer’s role is expected to be. There is a great deal of prescriptive literature providing tools to advise designers on how to make more sustainable design decisions. Yet there is debate regarding how decisions are or should be made, who makes design decisions related to sustainability, and who is responsible for how sustainable product outcomes are. How these concepts are theorised in design, and how practitioner guidance on decision-making in sustainable design is framed by campaign groups, is likely to influence how design is done in practice. There is therefore a need to find out how designers are navigating expectations that they should be doing more sustainable design. There is a key gap in empirical literature of gathering and analysing designers’ accounts of how decision-making, values, and responsibility come into their work from their own perspectives. To start to fill this gap, I collected instances of interactional talk involving product designers’ verbal accounts in two different contexts in 2020. I carried out sixteen semi-structured interviews with an international sample of sustainability-focused product designers, asking questions about decision-making, values, and responsibility in specific recent design projects. I selected seven recordings of panel discussions at design conferences with a focus on sustainability from YouTube, based on their relevance to the concepts of decision-making, values, and responsibility. These two types of data allow the identification of similarities in ways of talking to others about the same topics in both private and public settings. I analysed extracts of the verbal data using discursive psychology, a method that has been specifically developed to analyse interactions, treating talk as action, and commonly seeking to respecify how psychological concepts are understood. In the thesis, I present my analysis of how decision-making, values, and responsibility related to sustainability are constructed and managed in the designers’ accounts. This enables insights into how designers navigate the expectations that they should be making more sustainable design decisions. My analysis shows: 1) The designers manage the delicateness of decision-making, values, and responsibility in design in different ways. For example, participants either reject or orient to expectations regarding how design decision-making should be done, often contradicting themselves. Participants orient to the idea of values influencing their decisions but focus on explaining where values came from rather than how they influence. They negotiate expectations of responsibility by either deflecting or assuming it, depending on the framing of questions asked. 2) Participants take opportunities to portray their identities as sustainability-focused designers, depicting longstanding commitment. 3) When the designers portray a lack of agency to make sustainability-relevant design decisions, they then claim agency through focusing on their role in influencing and ‘pushing’ others. Thus, the complexity for designers of managing expectations, personal commitment, and limited agency related to making products more sustainable in professional settings is portrayed. The practical and theoretical contributions of these findings are provided, outlining how authors and practitioners who seek to make design more sustainable should carefully consider the expectations built into the way they frame their arguments and advice. Overall, this thesis demonstrates the usefulness of interdisciplinary research for providing novel insights, through examining sustainable design using a contemporary, qualitative method from psychology.
Keywords: Sustainable design; Product designers; Discursive psychology; Agency; Decision-making; Personal values; Responsibility; Identity